2022
DOI: 10.1021/acs.energyfuels.1c03878
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pore-Scale Visualization during CO2 Injection into CH4 Hydrate-Saturated Porous Media

Abstract: A better understanding of the mobility of the CO2 phase and the sweep within the CH4 hydrate-bearing sediments is required for the success of CO2 storage and concurrent CH4 production. In this work, we investigate the injectivity of CO2 in CH4-hydrate-saturated porous media and the subsequent dissociation of CH4 / CO2 mixed hydrate at the pore level. A total of six pore-scale visualization experiments were performed using a high-pressure water-wetted silicon wafer-based micromodel whose pore network resembles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The study by Xu et al reported that the production well should be in the upper layer of the reservoir for larger particle size sediments, whereas for sediments with smaller particles, the production well should be located in the bottom layer of the reservoir. Pandey et al evaluated the effects of the liquid CO 2 injection on the evolution of morphology in the CH 4 hydrate system based on pore-level visualization. The findings are relevant to the proposed CO 2 injection into CH 4 hydrate as a novel approach to store CO 2 while generating CH 4 .…”
Section: Energymentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Xu et al reported that the production well should be in the upper layer of the reservoir for larger particle size sediments, whereas for sediments with smaller particles, the production well should be located in the bottom layer of the reservoir. Pandey et al evaluated the effects of the liquid CO 2 injection on the evolution of morphology in the CH 4 hydrate system based on pore-level visualization. The findings are relevant to the proposed CO 2 injection into CH 4 hydrate as a novel approach to store CO 2 while generating CH 4 .…”
Section: Energymentioning
confidence: 99%
“…Pandey et al evaluated the effects of the liquid CO 2 injection on the evolution of morphology in the CH 4 hydrate system based on pore-level visualization. The findings are relevant to the proposed CO 2 injection into CH 4 hydrate as a novel approach to store CO 2 while generating CH 4 . Li et al combined microfocus X-ray computed tomography and a pore network model to investigate the effect of hydrate dissociation on gas trapping and hysteresis in capillary pressure in different wettability systems.…”
Section: Energymentioning
confidence: 99%
“…Wolfcamp shales (high carbonate) show an increased pore volume, which is potentially good for storage. Pandey et al 35 utilized a powerful tool and found that CO 2 injection dissolves some initial hydrate and moves liquid around and free gas, and slow injection takes longer to plug pores, which is good for CO 2 capture. Gao et al 36 delves into injecting CO 2 in tight oil, which can be a doubleedged sword.…”
Section: Introductionmentioning
confidence: 99%